Status of healthcare workers after comprehensive reform of urban public hospitals in Beijing, China: sustainable supply, psychological perception, and work outcomes - Jianwei Deng; Yangyang Sun; Run Lei; Yilun Guo; Jian Liu; Tianan Yang (BMC, 2019)
Abstract Background Healthcare reform in China has attracted worldwide interest and reached a new juncture. In an attempt to improve healthcare quality and patient satisfaction, the government of Beijing introduced comprehensive reform of urban public hospitals in 2016 and implemented new policies on personnel, compensation, management, and diagnosis and treatment. As the agents of healthcare service, and a target of reform measures, healthcare workers were greatly affected by these reforms but have not been carefully studied. Methods This study used mean value analysis, variance analysis, and qualitative content analysis to investigate the status of healthcare workers after comprehensive reform of urban public hospitals in Beijing. Results We found a gradual but constant increase in the number of healthcare workers in poor health in Beijing public hospitals. After the reforms, this population reported high challenge stress, public service motivation, job satisfaction, job performance and quality of healthcare, moderate presenteeism, and low hindrance stress and turnover intention. The status of healthcare workers differed by subgroup and changed during the reform process. Conclusions Our study provides data useful for policy recommendations regarding the implementation and extension of future reforms and offers important lessons for developing and developed countries that are reforming public hospitals to improve efficiency and reduce costs.